Novel herbs and drugs for endometriosis management: A review on current and futuristic therapies - Komal S; Harikrishnan N; Gejalakshmi S; Kayalvizhi S; Hemamalini Baskaran; Priyanka J; Mohan Kumar A; Sriram GM (International Journal of Research in Pharmaceutical Sciences, 2021)
A disorder with estrogen dependency comprising of inflammatory lesions outside the uterus, causing pain and inflammation in pelvis and affecting women of reproductive age with infertility and post reproductive age is endometriosis. Endometriosis is viewed as public health issue with a major impact on quality of life of women. Medically advanced computational and chemical treatments are available to treat the progression of the disease by diagnostic imaging, clinical examinations, imaging and laparoscopy often leading to immediate surgery. A warrantable rethinking on the diagnosis and management of endometriosis is to be assessed and medical treatments should be considered as first-line option for therapeutic relief for endometriosis by suppressing the systemic estrogen levels providing desirable efficacy and safety, prior to performing endometriosis surgery. The aim of this review is to describe natural products, hormonal and non-hormonal compounds that suppress the progression of endometriosis. Various herbal, conventional and traditional therapies are investigated to treat gynecological disease, endometriosis. The information in this paper include various studies assessing the use of novel treatments in addition to the herbal and hormonal products in the endometriosis therapy. Most of the studies involved were in scrutinizing the pharmacological activity profiles of various sources of drugs in endometriosis treatment, hormonal drugs involved suppression and regulation of various hormones along with various factors like anti-inflammatory, anti-oxidant, anti-proliferative and apoptotic, anti-angiogenic, anti-invasive, immunomodulatory, and estrogen modulating activity.